Performance of Physiological Characteristics and Content of Sweet Corn Mutant Some Lines of Sugar (Zea mays L. saccharate Sturt.) Sied of Gamma Ray Irradiation in M1 Generation. - Muhammad Luthfi Teguh Pratama (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2021)
ABSTRACT Sweet corn has a multipurpose function. The need for this commodity continues to increase every year, while the sied of production produced by farmers have not been able to meet the needs. One effort to increase sweet corn production is by mutation techniques to assemble the genetic traits of varieties. This study aims to obtain the best interaction between sweet corn lines and gamma ray irradiation doses on physiological characteristics and sugar content in maniss corn plants (Zea mays L saccharata Sturt). This research was carried out in PT. Pertani, Sirnabaya Village, East Telukjambe sub District, Karawang start in May 2019 until September 2019. The method used is an experimental method using a factorial randomized block design. There are two factors consisting of 20 treatments. The first factor was the sweet corn with replications consisting of 5 lines, the second factor is the dose of gamma ray irradiation consisting of 4 levels. The effect of the treatment was analyzed by analysis of variance, to find out the best treatment continued with the DMRT (Duncan Multiple Range Test) test at 5% level. There was the best interaction between sweet corn lines and gamma ray irradiation dose, the best effect was on G1M1 treatment in almost all parameters of observation (plant height, number of leaves, weight of cobs with hurt, weight of cobs without hurt, long of cobs with hurt, long of cobs without hurt, diameter of cobs with hurt, diameter of cobs without hurt, sugar content, leaf area, leaf area index, crop yields). Keywords : lines, sweet corn, gamma ray irradiation, sugar content